Adverse events of postoperative thoracic epidural analgesia: A retrospective analysis of 7273 cases in a tertiary care teaching hospital. Issue 10 (October 2016) - von Hösslin, Thomas; Imboden, Paul; Lüthi, Andreas; Rozanski, Marta J.; Schnider, Thomas W.; Filipovic, Miodrag
Abstract : BACKGROUND: Thoracic epidural analgesia is a well established technique for postoperative pain relief after major abdominal and thoracic surgery. Safety remains a major concern because of serious adverse events including epidural haematoma, abscess and permanent neurological deficit. OBJECTIVE: The aim of this study was to evaluate the incidence and the long-term outcome of serious adverse events associated with thoracic epidural analgesia. DESIGN: Retrospective cohort study. SETTING: The study was conducted at a single institution, a tertiary care teaching hospital. Data were collected over a 10-year period from 2003 until 2012. PATIENTS: Data from 7430 patients were prospectively entered into a standardised acute pain service database. A total of 7273 study participants met the inclusion criteria and were included in the final analyses. The inclusion criteria involved surgical patients receiving a postoperative thoracic epidural analgesia catheter treatment for pain control. Exclusion criteria were defined as obstetric, non-surgical, non-epidural analgesia patients and epidural analgesia catheters that had not been placed by an anaesthesiologist. MAIN OUTCOME MEASURES: The database was queried for serious adverse events which were defined as spinal or epidural haemorrhage; spinal or epidural abscess; permanent neurological deficits; cardiac arrest; death and incomplete removal of the epidural analgesia catheter. Patients' charts were comprehensively reviewed in case of a major adverse event. Patients with an unclear outcome received a mailed questionnaire or were contacted by telephone to determine long-term sequelae. RESULTS: Seven serious adverse events were identified: epidural abscess [ n  = 1; incidence 1 : 7273 (0.014%, 95% confidence interval, CI, 0 to 0.08%)], persistent neurological damage [ n  = 1; incidence 1 : 7273 (0.014%, 95% CI, 0 to 0.08%)], cardiac arrest [ n  = 1; incidence 1 : 7273 (0.014%, 95% CI, 0 to 0.08%)] and catheter breakage leaving a catheter fragment in situ [ n  = 4; incidence 1 : 1818 (0.055%, 95% CI, 0.01 to 0.14%)]. Apart from the one patient with persistent neurologic deficit, the patients with serious adverse events associated with thoracic epidural analgesia in our cohort suffered no long-term consequences. CONCLUSION: In our single-centre study of thoracic epidural analgesia, serious adverse events occurred in 0.1% cases (1 : 1000), whereas long-term outcome was compromised in 0.014% (1.4 : 10 000) which is similar to the serious adverse event rates and outcomes reported in the current literature.